Unraveling patient satisfaction, associated factors, and dissatisfaction reasons in the provision of health care services for rural communities in Bangladesh: A cross-sectional investigation - Abu Bakkar Siddique; Sudipto Deb Nath; Sayed Mohammad Rasel; Chandon Roy; Md Mohtasim Monim; M. Ziaul Amin (Elsevier, 2024)
Background: Access to high-quality healthcare is a fundamental right, but rural communities in Bangladesh face challenges in accessing such services. Patient satisfaction plays a crucial role in healthcare outcomes. Identifying factors influencing satisfaction is vital for targeted interventions. Methods: A cross-sectional investigation was conducted in rural areas of Sirajganj, Rajshahi, Bangladesh, from April to June 2023. Convenient sampling was employed, and face-to-face interviews were conducted using a semi-structured questionnaire. A total of 411 participants were included in the final analysis. Descriptive statistics, as well as bivariate and multivariable logistic regression analyses, were carried out using SPSS software. Results: Most unmarried participants (mean age: 41.93 ± 14.54 years; age range: 18-88 years) had primary education and a family income below 15,000 BDT. Among them, 80.3 % reported dissatisfaction with treatment. Significant factors linked to dissatisfaction included low education, being a businessman, living in nuclear families, daily physical exercise, difficulty accessing healthcare, average doctor-patient communication, high treatment costs, long waiting times, government hospital services, proximity to healthcare centers, lack of follow-up services, and absence of Telemedicine or M-health services. Conclusion: This study identifies key factors affecting patient satisfaction in rural Bangladesh. Interventions should focus on improving doctor-patient communication, reducing treatment costs and waiting times, enhancing access to healthcare and follow-up services, and incorporating Telemedicine or M-health services. Special attention is needed for businessmen, nuclear family residents, those who exercise daily, and patients using government hospitals or living near healthcare centers, as these groups report higher dissatisfaction.